β-Lactam Therapeutic Drug Monitoring in Critically Ill Patients: Weighing the Challenges and Opportunities to Assess Clinical Value - Thomas J. Dilworth, PharmD; Lucas T. Schulz, PharmD; Scott T. Micek, PharmD; Marin H. Kollef, MD; Warren E. Rose, PharmD (Critical Care Explorations, 2022)
OBJECTIVE:. β-lactams are the cornerstone of empiric and targeted antibiotic therapy for critically ill patients. Recently, there have been calls to use β-lactam therapeutic drug monitoring (TDM) within 24–48 hours after the initiation of therapy in critically ill patients. In this article, we review the dynamic physiology of critically ill patients, β-lactam dose response in critically ill patients, the impact of pathogen minimum inhibitory concentration (MIC) on β-lactam TDM, and pharmacokinetics in critically ill patients. Additionally, we highlight available clinical data to better inform β-lactam TDM for critically ill patients. DATA SOURCES:. We retrospectively analyzed patients admitted for sepsis or septic shock at a single academic medical center who were treated with β-lactam antibiotics. STUDY SELECTION:. Indexed studies in PubMed in English language were selected for review on topics relative to critical care physiology, β-lactams, pharmacokinetics/pharmacodynamics, TDM, and antibiotic susceptibility. DATA EXTRACTION:. We reviewed potentially related studies on β-lactams and TDM and summarized their design, patients, and results. This is a synthetic, nonsystematic, review. DATA SYNTHESIS:. In the retrospective analysis of patients treated with β-lactam antibiotics, approximately one-third of patients received less than 48 hours of β-lactam therapy. Of those who continued beyond 48 hours, only 13.7% had patient-specific factors (augmented renal clearance, fluid overload, morbid obesity, and/or surgical drain), suggesting a potential benefit of β-lactam TDM. CONCLUSIONS:. These data indicate that a strategy of comprehensive β-lactam TDM for critically ill patients is unwarranted as it has not been shown yet to improve patient-oriented outcomes. This review demonstrates that β-lactam TDM in the ICU, while laudable, layers ambiguous β-lactam exposure thresholds upon uncertain/unknown MIC data within a dynamic, unpredictable patient population for whom TDM results will not be available fast enough to significantly affect care. Judicious, targeted TDM for those with risk factors for β-lactam over- or underexposure is a better approach but requires further study. Clinically, choosing the correct antibiotic and dosing β-lactams aggressively, which have a wide therapeutic index, to overcome critical illness factors appears to give critically ill patients the best likelihood of survival.